Indeno[1, 2, 3, 4‐pqra]Perylene: A Medium‐Sized Aromatic Hydrocarbon Exhibiting Full‐Range Visible‐Light Absorption. Issue 2 (7th December 2021) - Kato, Masaki; Fukui, Norihito; Shinokubo, Hiroshi
Abstract: We report the synthesis and properties of indeno[1, 2, 3, 4‐ pqra ]perylene, which was prepared by the fusion of one anthracene unit with one naphthalene unit via three carbon‐carbon bonds. The synthetic route through two‐fold C−H arylation enabled not only the synthesis of unsubstituted indenoperylene, but also rapid access to its arylated derivatives on the gram scale. Indenoperylene is a medium‐sized aromatic hydrocarbon with the composition C24 H12 that is isomeric to coronene. Nevertheless, its absorption covers the entire visible region owing to its small HOMO‐LUMO gap. Furthermore, indenoperylene exhibits high stability despite the absence of peripheral substituents. We propose that the unique electronic structure of indenoperylene originates from the coexistence of an electron‐withdrawing subunit (benzoaceanthrylene) and an electron‐donating subunit (perylene). The electronic properties of indenoperylene were modulated via post‐functionalization through regioselective bromination. The current research demonstrates that indenoperylene is a promising candidate as a main skeleton for near‐infrared‐responsive and redox‐active materials. Abstract : The synthesis and properties of indeno[1, 2, 3, 4‐ pqra ]perylene are described. Indenoperylene is a medium‐sized aromatic hydrocarbon with the composition C24 H12 that is isomeric to coronene. Nevertheless, its absorption covers the entire visible region owing to its small HOMO‐LUMO gap. Furthermore, indenoperylene exhibits high stability despite the absence of peripheral substituents.